Kajian Disfemisme Akun Instagram @Kompascom - Musliana Dewi; Alber Alber (UIR Press, 2023)
With the ease of freedom to express ideas, aspirations and opinions on social media without realizing it, these ideas or opinions have dysphemism or have a rough meaning. The source of the community's legibility affects the pattern of language. This study discusses dysphemism in the @kompascom Instagram account. The purpose of this study is to describe in depth the value of dysphemism and the meaning of dysphemism in the Instagram account @kompascom January 1-31 2021 edition. The theory used is the theory of Fiiarum and Savitri (2018) and Abdul Chaer (2009). This research method is content analysis method. This study uses a qualitative research approach. The source of this research data is the news text in the @kompascom Instagram account edition January 1-31 2021. This type of research is library research. The data collection techniques of this research are documentation techniques and hermeneutic techniques. The data studied were documented by reading, recording, summarizing and classified based on categories according to the theory used. The results obtained are 39 data. Based on the value of the sense of dysphemism, it is divided into the value of disgusting taste, the value of terrible taste, the value of creepy taste, the value of embarrassing taste and the value of scary taste. Based on the meaning of dysphemism, it is divided into 2, namely denotative meaning and connotative meaning. The use of dysphemism in the @kompascom account has more value for fear of negative depictions to make it look bad for an object or event and uses more denotative meanings in describing meaning according to reality. In this study, it was found that the value of dysphemism was 39 data, 3 data value of disgusting taste, 11 data value of terrible taste, 4 data value of creepy taste, 6 data value of shameful taste and 15 data value of scary taste. The form of the meaning of dysphemism contained in this study is the meaning of denotative dysphemism with 30 data and connotative meaning of 9 data.